2018
DOI: 10.1161/jaha.117.007603
|View full text |Cite
|
Sign up to set email alerts
|

Use of Direct Oral Anticoagulants in Canadian Primary Care Practice 2010–2015: A Cohort Study From the Canadian Primary Care Sentinel Surveillance Network

Abstract: BackgroundAs questions have been raised about the appropriateness of direct oral anticoagulant (DOAC) dosing among outpatients with atrial fibrillation, we examined this issue in patients being managed by primary care providers.Methods and ResultsThis was a retrospective cohort new‐user study using electronic medical records from 744 Canadian primary care clinicians. Potentially inappropriate DOAC prescribing was defined as prescribing lower or higher doses than those recommended by guidelines for patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 20 publications
4
26
5
Order By: Relevance
“…In a real-world registry in Spain, the rate of underdosing and overdosing of DOAC therapy was 17.5% (93/530) and 14.9% (79/ 530), respectively [16]. Other retrospective studies conducted abroad indicate that 5.4-17.4% patients are prescribed inappropriate reduced doses of DOACs (Additional file 1: Table S2) [17][18][19][20]. In our study, it was found that the rate of underdosing has been decreasing every year.…”
Section: Discussionmentioning
confidence: 99%
“…In a real-world registry in Spain, the rate of underdosing and overdosing of DOAC therapy was 17.5% (93/530) and 14.9% (79/ 530), respectively [16]. Other retrospective studies conducted abroad indicate that 5.4-17.4% patients are prescribed inappropriate reduced doses of DOACs (Additional file 1: Table S2) [17][18][19][20]. In our study, it was found that the rate of underdosing has been decreasing every year.…”
Section: Discussionmentioning
confidence: 99%
“…refills every 1–3 months vs renal function assessment every 3–12 months depending on baseline renal function), the pharmacist may not be seeing the patients at point of refill and some pharmacists may perceive this as duplicating a task performed by the physician. However, real‐world evidence shows that approximately 10% of patients prescribed DOACs are receiving an inappropriate dose, including excess dosing in 43% of patients with a renal indication for a lower dose . This inappropriate dosing was associated with a greater risk of harm, including major thrombotic and bleeding events .…”
Section: Discussionmentioning
confidence: 99%
“…However, real-world evidence shows that approximately 10% of patients prescribed DOACs are receiving an inappropriate dose, including excess dosing in 43% of patients with a renal indication for a lower dose. [4][5][6] This inappropriate dosing was associated with a greater risk of harm, including major thrombotic and bleeding events. 5 These observations highlight a key role for pharmacists to improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations